Hydrogen sulfide measurements in air by passive/diffusive samplers and high-frequency analyzer: A critical comparison. (September 2016) - Venturi, S.; Cabassi, J.; Tassi, F.; Capecchiacci, F.; Vaselli, O.; Bellomo, S.; Calabrese, S.; D'Alessandro, W.
Abstract: In this study, hydrogen sulfide (H2 S) measurements in air carried out using (a) passive/diffusive samplers (Radiello ® traps) and (b) a high-frequency (60 s) real-time analyzer (Thermo ® 450i) were compared in order to evaluate advantages and limitations of the two techniques. Four different sites in urban environments (Florence, Italy) and two volcanic areas characterized by intense degassing of H2 S-rich fluids (Campi Flegrei and Vulcano Island, Italy) were selected for such measurements. The concentrations of H2 S generally varied over 5 orders of magnitude (from 10 −1 –10 3 μg/m 3 ), the H2 S values measured with the Radiello ® traps (H2 SR ) being significantly higher than the average values measured by the Thermo ® 450i during the trap exposure (H2 STa ), especially when H2 S was <30 μg/m 3 . To test the reproducibility of the Radiello ® traps, 8 passive/diffusive samplers were contemporaneously deployed within an 0.2 m 2 area in an H2 S-contaminated site at Mt. Amiata (Tuscany, Italy), revealing that the precision of the H2 SR values was ±49%. This large uncertainty, whose cause was not recognizable, is to be added to that related to the environmental conditions (wind speed and direction, humidity, temperature), which are known to strongly affect passive measurements. The Thermo ® 450i analyzer measurements highlighted the occurrence of short-term temporal variations of the H2 S concentrations, with peak values (up to 5732 μg/m 3 ) potentially harmful to the human health. The Radiello ® traps were not able to detect such temporal variability due to their large exposure time. The disagreement between the H2 SR and H2 STa values poses severe concerns for the selection of an appropriate methodological approach aimed to provide an accurate measurement of this highly toxic air pollutant in compliance with the WHO air quality guidelines. Although passive samplers may offer the opportunity to carry out low-cost preliminary surveys, the use of the high-frequency H2 S analyzer is preferred when an accurate assessment of air quality is required. In fact, the latter provides precise real-time measurements for a reliable estimation of the effective exposure to hazardous H2 S concentrations, giving insights into the mechanisms regulating the dispersion of this air pollutant in relation to the meteorological parameters. Highlights: H2 S measurements with Radiello ® traps and Thermo ® 450i analyzer are compared. The disagreement between the two methods increases at low H2 S concentrations. Peak values cannot be detected using the Radiello ® traps. The Thermo ® 450i analyzer provides detailed records of H2 S temporal variations. Real-time H2 S measurements are more suitable for air quality monitoring.